Covalent Post‐Assembly Modification: A Synthetic Multipurpose Tool in Supramolecular Chemistry. Issue 6 (12th June 2020) - Zeng, Haoxiang; Stewart‐Yates, Luke; Casey, Louis M.; Bampos, Nick; Roberts, Derrick A.
Abstract: The use of covalent post‐assembly modification (PAM) in supramolecular chemistry has grown significantly in recent years, to the point where PAM is now a versatile synthesis tool for tuning, modulating, and expanding the functionality of self‐assembled complexes and materials. PAM underpins supramolecular template‐synthesis strategies, enables modular derivatization of supramolecular assemblies, permits the covalent 'locking' of unstable structures, and can trigger controlled structural transformations between different assembled morphologies. This Review discusses key examples of PAM spanning a range of material classes, including discrete supramolecular complexes, self‐assembled soft nanostructures and hierarchically ordered polymeric and framework materials. As such, we hope to highlight how PAM has continued to evolve as a creative and functional addition to the synthetic chemist's toolbox for constructing bespoke self‐assembled complexes and materials. Abstract : Very versatile : Covalent post‐assembly modification in supramolecular chemistry continues to evolve as a versatile multipurpose tool for modular derivatization, template synthesis, covalent trapping of unstable structures, and triggering of controlled structural transformations between different assembled architectures. This Review aims to highlight recent developments in post‐assembly modification methods that can be used to access interesting supramolecular structures and behaviors.